O Guia Didático CEL-LOGIC: a integração do pensamento computacional e da lógica de programação no ensino médio integrado - Cardinale, Carolina Leite (2025)
This article aims to present the foundations for the development of an Interactive Didactic Guide called CEL-LOGIC, designed for teaching Programming Logic and Computational Thinking (CT) in the context of Integrated High School with a focus on Technical Informatics. Using the App Inventor platform, CEL-LOGIC was designed to help students overcome difficulties in learning basic programming concepts and to stimulate cognitive skills related to CT. The pedagogical and technological guidelines for the development of mobile applications were based on curricular and institutional documents from a state technical school in São Paulo. The results highlighted the potential of CEL-LOGIC for digital education in Basic Education.